Focusing Attention to Improve Throwing Skills in Children With Autism Spectrum Disorder: Exploring the Influence of Working Memory - Qaith Mohammad Ramadan; Ayoob Sabaghi; Ali Heirani (Occupational Therapy International)
This study is aimed at investigating the impact of internal and external attention focus on learning a throwing skill in children with autism, as well as the relationship between working memory and learning rate. Twenty-four children aged 6–8 years with autism were assigned to internal and external attention groups. Participants performed a throwing task while their working memory was assessed using Cornoldi’s working memory test. The data was analyzed using ANOVA with repeated measures involving two attention instructions and five blocks during the acquisition stage. An independent t-test was conducted during the retention phase. Furthermore, a Pearson correlation test was utilized to explore any potential relationship between working memory and performance in both the acquisition and retention stages. Data analysis revealed no significant difference between the internal and external attention groups during the acquisition phase (p>0.05), but a significant difference was found in the retention phase (p<0.05). There was no correlation between working memory and learning outcomes (p>0.05). The results suggest that internal attention may enhance motor learning in children with autism, and reducing working memory load does not necessarily favor external attention.